Lived Experiences of English Pre-Service Teachers on Public Speaking Anxiety: A Speech Improvement Program - Arman Navarro (Journal of English as A Foreign Language Teaching and Research, 2025)
This study explored the lived experiences of 10 English pre-service teachers with public speaking anxiety.  Hermeneutic phenomenology guided the qualitative research design, employing interviews and focus group discussions to gather data. Findings revealed seven key themes: language skill gaps, attitudes toward second language learning, low self-confidence hindering speaking, improved teaching strategies, the importance of a supportive, nonjudgmental environment, and the influence of varied internal and external factors on anxiety. The study highlights the need for educators to foster supportive learning environments that mitigate anxiety and encourage confident public speaking. To address this, the researcher proposes "SPEECH: Strategies for Public Speaking Empowerment and Confidence Heightening," a project designed to equip learners with effective public speaking skills and reduce anxiety through targeted activities. This research provides valuable insights into the complexities of public speaking anxiety among preservice teachers, offering practical implications for pedagogical approaches and interventions.